EFEK SUPLEMEN BESI TERHADAP PENINGKATAN HB DAN INDEK ERITROSIT IBU HAMIL - Widarsa, Tangking; Weta, Wayan; Widhiartini, Ida Ayu Alit (ARCHIVE OF COMMUNITY HEALTH, 2012)
To study the e? ect of iron supplement equivalent to 60 mg elemental iron and 0.25 mg folic acid to the erythrocyte indexes and anemia among pregnant mothers.A pretest-pos! est community trial was carried out among pregnant mothers who were absent of bleeding history and other blood disorders and gestation’s age were under 24 weeks. Iron tablets equivalent to 60 mg elemental iron and 0.25 mg folic acid were given to the mothers every day until 8 weeks long. Hb, MCV, MCH, and MCHC were evaluated twice before intervention and a$ er intervention. The changes were analyzed using t-test and X 2 test at 0.05 signi? cance level. Before intervention, almost 78.23% of pregnant women su? ering from iron de? ciency (MCH < 27 pg/cell) and 35.28% were anemic (Hb < 11 g/dl). The proportion of su? ering iron de? ciency and anemia signi? cantly decreased a$ er intervention (p < 0.05). The proportion of su? ering iron de? ciency decreased to 27.43% and anemia decreased to 9.35%. The mean of Hb, MCH and MCHC signi? cantly increased a$ er intervention (p < 0.05), but there was no changes on MCV (p > 0.05). More then 2/3 of the pregnant mothers su? ered from iron de? ciency and 1/3 were anemic. Iron supplement signi? cantly increased the erythrocyte indexes and reduced the prevalence of anemia among pregnant mothers. Therefore, it is important to continue iron supplement program and it will be more e? ective when ? rst introduced at pre-maternal period.
Keywords: Iron Supplement, Erythrocyte Indexes, Anemia of Pregnant Mothers